A avaliação em sala de aula: quais as dificuldades para a formação do professor do ensino básico? - Rojas, Hugo de Los Santos (2007)
The conceptions and practices of teachers regarding educational assessment or educational evaluation of their pupils have been object of critical concerns for many years, on the part of innumerable educational researchers. However, looking at the conditions that are offered to the teachers for learning the complex procedure of evaluation, it can be observed that its pre-service training does not contemplate it, that there are few consistent chances of in-service training on the theme, that the critics generally have been writing more about the difficulties than have offered realistic solutions, and that the available models or approaches on what must be the process of evaluation are not concordant between them nor are they completely structured for the immediate application in classroom. Considering this picture, this study has the purpose of investigating what the difficulties are in the formation of the teacher for the evaluation of his pupils (also known as classroom assessment, pedagogical assessment classroom evaluation). To analyze the mentioned situation, we consider in the study a great amount of evaluation approaches, taken from the Brazilian, American or European academic discourses, as well as research on the formation of teachers regarding the difficulties faced for them in their education, continued or initial (in-service or pre-service training). We have interviewed 12 private school teachers of the city of São Paulo, from different subjects; they were considered as very involved in the process of learning on evaluation, by directors and/or coordinators of their schools. Based on the analysis of the teachers speech and in the presented theories, it was verified that the difficulties are of different orders: the lack of pre-service training for the evaluation process, inadequate pre-service training for teaching, the dispersion of evaluative approaches, the lack of material adjusted for the study of the different evaluative approaches, and questions related to the structure of the teaching work - number of pupils, the role of the institution where the teacher works and the relationship between the group of teachers